2015
DOI: 10.1155/2015/305142
|View full text |Cite
|
Sign up to set email alerts
|

Double Orifice Mitral Valve and Bicuspid Aortic Valve: Pieces of the Same Single Puzzle?

Abstract: Double orifice mitral valve is a very rare congenital abnormality. Well known associations of this pathology with other congenital lesions point to a complex and central pathophysiological mechanism leading to a sequence of pathologies. These associations have long been realized and arbitrarily defined as Shone complex. We would like to present a 21-year-old patient with double orifice mitral valve associated with bicuspid aortic valve, with a brief review of the literature on possible central mechanisms leadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…The anterior mitral valve leaflet in our bicuspid aortic valve cohort measured statistically significantly longer when compared with the control group ( P < 0.001). This was in keeping with our visual impression as well as supporting the findings of a previous smaller study ( 10 ). In our cohort, none of the patients had systolic anterior motion of this abnormally long anterior mitral valve leaflet, and therefore no functional implications of this abnormality were noted.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The anterior mitral valve leaflet in our bicuspid aortic valve cohort measured statistically significantly longer when compared with the control group ( P < 0.001). This was in keeping with our visual impression as well as supporting the findings of a previous smaller study ( 10 ). In our cohort, none of the patients had systolic anterior motion of this abnormally long anterior mitral valve leaflet, and therefore no functional implications of this abnormality were noted.…”
Section: Discussionsupporting
confidence: 93%
“…However, several studies have shown what appears to be more than a coincidental link between bicuspid aortic valve and mitral valve prolapse ( 6 , 7 , 8 ) with an incidence as high as 5% reported in this setting by Schaeffer and coworkers ( 9 ). An association with rare congenital abnormalities of the mitral valve has been suggested, including a case report of a double orifice mitral valve in the setting of a bicuspid aortic valve ( 10 ). Minor structural abnormalities of the mitral valve in the setting of BAVs have also been reported with one small study showing an association with an abnormal anterior mitral valve leaflet ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the biomechanical properties of the valve, signaling pathways that regulate migration and differentiation of cellular components are thought to be responsible for the embryogenesis and pathogenesis of acquired valve diseases. It was reported that some genes involved in mitral and Open Journal of Veterinary Medicine aortic valve pathogenesis regulate general differentiation and morphogenesis of all valves [4]. For example, NOTCH-1 signaling involved in the pathogenesis of aortic valve disease has been shown to play important roles in normal valvulogenesis of all valves, by regulating the activity of various other genes and transcription factors [5].…”
Section: Case Presentationmentioning
confidence: 99%